"Post intubation Laryngeal injuries in a pediatric intensive care unit of tertiary hospital in India: A Fibreoptic endoscopic study". (June 2016) - Bharti, Bhartendu; Syed, Kamran Asif; Ebenezer, Kala; Varghese, Ajoy Mathew; Kurien, Mary
Abstract: Study objectives: To identify acute laryngeal injuries among pediatric patients intubated for more than 48 hours, and to correlate these injuries with clinical variables. Setting: Pediatric Intensive Care Unit (PICU) of a tertiary level hospital in India. Patients and Methods: Prospective, observational study. Thirty-four children meeting the inclusion and exclusion criteria were recruited into the study after obtaining informed consent from the parents. A bedside, flexible, fiberoptic laryngoscopy was done within the first 24 hours of extubation. Laryngeal injuries were documented and graded. Individual types of laryngeal injuries were correlated to the duration of intubation, size of the tube, the experience of the intubator and the patient's demographics. A repeat endoscopy was done in the outpatient department, 3-4 weeks after extubation, and findings noted. Results: 97% had acute laryngeal injury, of which 88% were significant. Erythema was the most common form of injury. Duration of intubation, with a mean of 4.5 days, showed a trend towards significance (p = 0.06) for association with subglottic narrowing. Laryngeal injuries were similar with both cuffed and uncuffed tubes. Age of the subject, size of the tube and skill level of the intubator did not correlate with the laryngeal injuries. 18% required intervention for post-extubation laryngeal lesions. Three (10%) children had post-extubation stridor, and of these, two needed surgical intervention (6%). Conclusion: Post-extubation laryngeal injuries are not uncommon. Fiberoptic endoscopy is an inexpensive and cost-effective tool for bedside evaluation of post-intubation status in pediatric larynx. Early diagnosis of post-intubation laryngeal injuries in children can prevent long term sequelae. Hence, post-extubation fiberoptic laryngoscopy should be done routinely in pediatric population.